MAQĀṢID AL-SYARῙ‘AH DALAM PENAWARAN PRODUK TAKAFUL WANITA: KAJIAN DI PENGENDALI TAKAFUL TERPILIH DI MALAYSIA: Maqāṣid al-Sharī‘ah in Offering Takaful Product for Women: A Study At Selected Takaful Operator in Malaysia - Ahmad, Nor Hanani; Ab Rahman, Asmak; Abd Rani, Nuurshiraathal Firdaws (Jurnal Syariah, 2017)
Since 2005 and recent years, takaful product is getting attention and growing substantially due to people are vulnerable to health risk especially women. Irony, the offering product takaful for women can managing their risk in financing, critical illness and so on. This study used content analysis on six product disclosure sheet of takaful that offered by four takaful operators. In addition, the researcher also have collected data through interview with Shariah officers, product development officers and takaful agents to understand the whole structure of the product. This finding of this study shows that takaful product for women is in line with Maqāṣid al-Sharī‘ah.